On the unilateral introduction of gold-backed currencies - Ansgar H. Belke; Ulrich Volz (Intereconomics, 2015)
Against the backdrop of an unstable international monetary system centred around the US dollar and very dim prospects of reforming this system, this article analyses the rationale for the unilateral introduction of gold-backed currencies and the challenges and problems associated with such a move. What would be the merits of unilaterally linking a currency to gold? How could this be managed, and what would be the risks? We argue that such a system would not bring price stability, as the country would not be able to control the international gold price, and that it would likely be exposed to volatile exchange rates.
Keywords: 330; Währungssystem; Goldstandard; Preisstabilität